Sendo a função f(x) = -4x² + 4x – 6, calcule:
a) f(2)
b) f(-1)
c) f(0)
Soluções para a tarefa
Respondido por
0
Resposta:
f(x)= -4^2x+4x-6
f(2)= -4^2.2+4.2-6
=16.2+8-6
=32+8-6
=40-6=34
f(-1)= -4^2.(-1)+4.-1-6
= 16.-1-4-6
= -16-4-6
=-20-6= -26
f(0)= -4^2.0+4.0-6
=16.0+4.0-6
=0+0-6=-6
Explicação passo-a-passo:
Perguntas interessantes
Geografia,
8 meses atrás
Matemática,
8 meses atrás
História,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás